The Effect of Dry needling and Muscle energy technique on Pain in Myofascial Trigger Point Syndrome (MTRPS) M.Upper Trapezius - Siti Sarah Bintang; Dani Hafiz Utomo; Simson Sinuhaji; Sabirin Berampu; Karnirius Harefa (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2024)
Background: Myofascial Pain Syndrome is a common health problem where the main cause is repetitive injury. Various interventions can be performed to reduce pain and symptoms from MTrPs, one of which is dry needling (DN) and muscle energy technique (MET). Purpose: of this study is to determine the effect of DN, MET, and combination of DN+MET on pain at MTrPs m.upper trapezius. Research method quantitative three groups pre and post test design. Sample was taken using total sampling technique and total of 48 people with MTrPs m.upper trapezius obtained. Numeric Rating Scale (NRS) used to measure pain intensity. The statistical tests used are Wilcoxon signed ranked test and the Mann-Whitney U. Results and discussion: effect of DN intervention with P-Value= 0.000 (P<0.05), MET P-Value= 0.000 (P<0.05), Combination of DN+MET P-Value= 0.000 (P<0.05). Comparison of DN with MET P-Value= 0.001 (P<0.05), DN with combination of DN+MET P-Value= 0.030 (P<0.05), MET with a combination of DN+MET P-Value= 0.000 (P<0.05). Conclusion: based on statistical result DN, MET, and the combination of DN+MET had the same effect on reducing pain at MTrPs m.upper trapezius, where the DN+MET combination proved to be more effective and more recommended in the treatment of MTrPs m.upper trapezius. Keywords: Myofascial Trigger Point Syndrome; Dry Needling; Muscle Energy Technique.